Effect of Embryo Thermal Stimulation on the Serum Levels of Immunoglobulins and Corticosterone, and Organ Histopathology of 1 day-old Broilers - F Flores; IA Nääs; RG Garcia; WMQ Quinteiro; LI Souza (Brazilian Journal of Poultry Science)
ABSTRACT Embryo thermal stimulation has been studied as a means to promote epigenetic changes and to improve broiler health and performance. This study aimed at evaluating immunoglobulin (IgM, IgG, and IgA) titers, serum corticosterone levels, and organ integrity of day-old male Cobb(r) and Ross(r) broilers. Embryos were submitted to hot and cold stimuli (thermal stimulation) on days 14-18 of incubation. The thermal manipulation treatments did not affect immunoglobulin titers of 1 day-old Cobb(r) or Ross(r) chicks, and caused severe bursal lesions (scores 3 and 4) in both strains. However, serum corticosterone levels of Cobb(r) chicks were higher when embryos were submitted to hot stimulus (+1.39ºC) compared with cold stimulus (+36 ºC). Serum corticosterone levels of Ross(r) chicks were not affected by embryo temperature manipulation. The only effect of broiler breeder age was observed on IgM titers of Cobb(r) chicks, which were higher in chicks from 33-wk-old breeders. Further studies are needed to detect the optimal period of embryo thermal stimulation.